Epidemiology, Clinical Characteristics, and Management Status of Hepatitis B: A Cross-sectional Study in a Tertiary Care Hospital at Karachi, Pakistan - Butt, Nazish (Cureus, 2019)
Background Hepatitis B virus (HBV) infection is a serious health problem in Pakistan. In view of the serious socioeconomic consequences, identifying patient characteristics and the current treatment for the disease will enhance HBV regulation and its medical management. Aims To describe the epidemiology, clinical characteristics, and current management status of patients infected by HBV. Methods We undertook an observational, cross-sectional, and epidemiological study at the Jinnah Postgraduate Medical Centre, Karachi, during the period from January 2014 to November 2017. Male and female patients of any age and with documentation for an HBV infection were eligible for inclusion in the study. An HBV infection was defined as a positive hepatitis B surface antigen test. Results A total of 500 patients were analyzed. The mean age at presentation was 29.86±13.68 years. The majority of the patients (25.6%) were ethnically Sindhi followed by Pathan (24.4%), indicating a high prevalence among the rural-based population of Pakistan. The mean duration of the disease was 3.51±4.46 years. The most common cause for the spread was positive family history (40.4%) followed by roadside barbers (30.0%). Most patients were Child-Pugh (CP) class A (84.6%) and the median Modified End-Stage Liver Disease (MELD) score was 7. Upper gastrointestinal bleeding was the most frequent hepatic complication (6.2%). Antiviral medications had been received by 18.6% of patients previously. Peg-interferon (6.0%) was the major antiviral medication prescribed to treatment-experienced patients. Conclusions This observational, real-life study has identified some gaps between clinical practice and guideline recommendations in Pakistan. To achieve better health outcomes, several improvements, such as disease monitoring and optimizing antiviral regimens, should be made to improve disease management.